Bioprecipitation of a calcium carbonate – Biofilm composite on the surface of concrete for the maintenance of nuclear reactor enclosures. (20th March 2020) - Lors, C.; Damidot, D.; Petit, L.; Legrix, A.; Tran, N.C.; Masson, B.
Highlights: Bioprecipitation of a calcium carbonate – biofilm composite was performed on concrete wall. Applied to a replica at 1/3 scale of a nuclear reactor enclosure that was subjected to pressurization. Leakage was reduced in areas where the concrete was not deformed during pressurization. Calcium carbonate – biofilm composite withstands an air flow with a pressure of 450 kPa. Abstract: Bioprecipitation of calcium carbonate – biofilm composite on the concrete surface by spraying a bacterial suspension can reduce the permeability of concrete especially in the presence of micro-cracks. This process was applied to a replica at 1/3 scale of a nuclear reactor enclosure that was then subjected to pressurization at 500 kPa. The effectiveness of bioprecipitation treatment was demonstrated in areas where deformations of the concrete during pressurization remained minimal. Additional laboratory tests confirmed that the calcium carbonate – biofilm composite bioprecipitated in a micro-crack can withstand an air flow with a pressure of 450 kPa.